Analisis Pemberitaan Kriminal Terhadap Wanita dan Remaja: Analisis Wacana Kritis Theo Van Leeuwen - Johar Amir (Seminar Nasional LP2M UNM, 2022)
Abstract. Human interaction is intended to be able to communicate with other people using various ways, both spoken and written. Criminal cases against women and adolescents are very interesting to analyze. Writing news about women and youth must use special treatment because if news writing is done openly it will have a negative impact, especially for underage youth. Given that the role of the media is very important in shaping the mindset of the community in responding to information that occurs around the community. Based on the background of the problems that have been described, researchers will reveal and identify carefully to obtain accurate information through a study entitled